Evaluation of Biomarkers of Oxidative Stress and Apoptosis in Patients With Severe Methotrexate Neurotoxicity: A Case Series. (September 2015) - Taylor, Olga A.; Hockenberry, Marilyn J.; McCarthy, Kathy; Gundy, Patricia; Montgomery, David; Ross, Adam; Scheurer, Michael E.; Moore, Ida M.
Central nervous system (CNS) treatment is an essential part of acute lymphocytic leukemia (ALL) therapy, and the most common CNS treatment is intrathecal (IT) and high-dose intravenous (IV) methotrexate (MTX). Treatment with MTX may cause neurotoxicity, which is often accompanied by neurologic changes, delays in treatment, and prolonged hospital stays. This article reports clinical presentations of 3 patients with severe MTX toxicity as well as levels of oxidative stress and apoptosis biomarkers in cerebrospinal fluid (CSF). Oxidative stress was measured by oxidized phosphatidylcholine (PC), oxidized phosphatidylinositol (PI), and F2 isoprostanes; apoptosis was measured by caspase 3/7 activity. Most consistent biomarker changes in all 3 cases were increases in caspase 3/7 and F2 isoprostanes prior to acute toxicity while increases in oxidized phospholipids occurred slightly later. Progressive increases in F2 isoprostanes and caspase 3/7 activity prior to and/or during acute toxicity suggests MTX induces oxidative stress and an associated increase in apoptosis. These findings support the role of oxidative stress in MTX-related neurotoxicity.